Explosive Eruptions With Little Warning: Experimental Petrology and Volcano Monitoring Observations From the 2014 Eruption of Kelud, Indonesia. (29th August 2019) - Cassidy, M.; Ebmeier, S. K.; Helo, C.; Watt, S. F. L.; Caudron, C.; Odell, A.; Spaans, K.; Kristianto, P.; Triastuty, H.; Gunawan, H.; Castro, J. M.
Abstract: Explosive eruptions that occur with little or no precursory unrest (less than a month) pose the greatest hazards from volcanoes to nearby populations. Here we focus on the preeruptive conditions for these explosive events, their triggers and how these eruptions evolve. We concentrate on Kelud volcano, where we have conducted a set of petrological experiments to understand preeruptive storage conditions for several recent eruptions. For the 2014 explosive eruption, we combine this with an analysis of interferometric synthetic aperture radar measured deformation. Our data suggest that both explosive and effusive eruptions at Kelud are sourced from a magma storage system at 2–4 km. However, explosive eruptions are fed by magma stored under relatively cool (~1000 °C) and water‐saturated conditions, whereas effusive eruptions are fed by slightly hotter (~1050 °C), water‐undersaturated magmas. We propose that the initial phase of the 2014 eruption was triggered by volatile overpressure, which then fostered top‐down decompression tapping discrete magma bodies. By compiling a global data set of monitoring signatures of explosive eruptions, we show that the onset of unrest rarely points to the shallow ascent of magma to the surface, as ascent mostly occurs in a matter of hours or minutes. We relate the timescale of preeruptive unrest to eruption triggering mechanisms, with yearly/decadal periods of unrest relating to magma injection events (which may or may not precede a magmatic eruption), whereas internal triggering (e.g., second boiling) of an already present, cooling magma body can lead to explosive eruptions with little warning. Key Points: Experimental petrology and InSAR data are combined for the first time showing a top‐down progression of the Kelud 2014 eruption Kelud magmas are stored at shallow depths (2‐4 km), mixed volatile conditions precede effusive eruptions, but explosive eruptions are water saturated A global monitoring data set demonstrates that explosive eruptions with little warning are common; duration of precursory signals may relate to eruption triggering mechanisms